InterPrEP: internet‐based pre‐exposure prophylaxis with generic tenofovir disoproxil fumarate/emtrictabine in London – analysis of pharmacokinetics, safety and outcomes1. Issue 1 (28th June 2017) - Wang, X; Nwokolo, N; Korologou‐Linden, R; Hill, A; Whitlock, G; Day‐Weber, I; McClure, MO; Boffito, M
Abstract : Objectives: The National Health Service in England (NHS England) does not provide pre‐exposure prophylaxis (PrEP) against HIV, forcing people to purchase generic versions on the internet. However, there are concerns about the authenticity of medicines purchased online. We established an innovative service offering plasma tenofovir (TFV) and emcitrabine (FTC) therapeutic drug monitoring for people buying generic PrEP online, to ensure that drug concentrations in vivo were consistent with those of propriety brands and previously published data. Methods: TFV/FTC concentrations were measured by ultra‐performance liquid chromatography ultraviolet detection. Evaluation of renal function and testing for HIV, hepatitis B virus (HBV) and hepatitis C virus (HCV) were also carried out, at baseline and every 3–6 months, with risk reduction advice. Results: A total of 293 individuals presented having purchased PrEP on the internet: 85% were white, 84% were taking daily PrEP, and 16% were event‐driven. Most were on generic TFV disoproxil fumarate (TDF)/FTC from Cipla Ltd. Median (range) TFV and FTC plasma concentrations were 104 (21–597) ng/mL and 140 (17–1876) ng/mL, respectively. All concentrations were above our established plasma TFV and FTC targets, based on previously published data. Renal function was normal in all evaluable individuals and no new cases of HIV, HBV or HCV infection were seen. Conclusions: In a population at high risk of HIV acquisition, who cannot yet access PrEP on the NHS, concentrations of TFV and FTC in generic formulations purchased over the internet were similar to (or slightly higher than) those measured in phase I studies with the original formulation from Gilead (Truvada™), which has demonstrated high levels of protection against HIV infection in previous PrEP clinical trials.